Perancangan Dan Pembuatan Prototype Catu Daya Tegangan Output Konstan Mengunakan Teknologi Konverter Step Up Kapasitas 320 Watt - Aldy Widodo; Suwitno Suwitno; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Boost converter is a dc to dc converter with an output voltage is higher than the voltage enter consisting of at least two a semiconductor ( transistors and a diode ) and a coil the depositary as an element of energy .Output boost converter in tentukkan by duty cycle of pwm that where enlarged duty cycle pwm and an output voltage is boost converter will go up and vice versa sags duty cycle pwm and an output voltage is boost converter down .On this thesis was built by a boost converter that could raise its 12v dc voltage into 55v dc and capable of flow the burden until 2.21a .The signal source pwm of mikrokontroller , switch mosfet use , inductance an air core and a diode use a kind of fast recovery to keep the level of voltage in useprisoners as a voltage divider befungsi as a series of feedback from output boost converter adcmikrokontroller to .Keywords : Boost Converter, DC To DC, PWM, Mosfet, diode Coil, Atemega 8535